(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
History, structure and possibilities of Dutor musical instrument.As one of the important means of educating the future generation in the spirit of national and moral values, it is of particular importance to introduce the national musical heritage through the art of playing instruments, in order to make it become the owner of allround aesthetic and artistic taste.